Determination of Greenhouse Time Constant Using Steady-state Assumption - Janius, Rimfiel; M. Jenkins, Bryan (Universiti Putra Malaysia Press, 2004)
A study was conducted to determine the applicability of a steady-state solution in predicting the changes in temperatures of the inside air and thermal mass of a bench-top-heated greenhouse in response to a step change in outside temperature. The steady-state analysis is simpler than that of the transient. However, a steady-state solution would only be appropriate if the time constant of the greenhouse is short compared to the total time under which the conditions outside the greenhouse are considered to be approximately constant. A lumped parameter method based on Albright et at. (1985) was used to estimate the time constant of the bench-top-heated greenhouse. The time constant was found to be very sensitive to the heat transfer coefficient, It.., between the thermal mass and inside air. A high value of It.. results in a longer time constant. For the estimated thermal mass properties, the value of It,. for the temporarily approximately constant outside conditions was calculated to be 0.23 Wm·2 K' for which the estimated time constant was about 0.75 hour. This time was reasonably short compared to the six-hour experimental period; thus the steady-state analysis was appropriate.